Morphological and mineral features of nZVI-induced precipitation on quartz particles. Issue 5 (30th April 2019) - Liu, Fuming; Zhou, Wan-Huan; Yi, Shuping; Geng, Xueyu
Abstract : This study investigated the morphological and mineral features of nano zero-valent (nZVI)-induced iron mineral precipitation on quartz particles. Lead was employed as the artificial contaminant, while quartz was used to mimic the inert solid mineral particles in soil. The characterisation indicate that iron minerals precipitated heterogeneously on the surface of quartz particles with plush-like and flake-like structures. They are made of deuterogenic plumbiferous minerals and ferriferous minerals, with amorphous structure. The curly flake-like mineral clusters had a scattered distribution on the surface of quartz along with the corroded nZVI aggregation. The thickness of the curly flake-like precipitation varied from 20 to 60 nm, and that of the plush-like precipitation from 20 to 35 nm. The generation of these iron mineral precipitations led to a slight increase in the average particle size and a decrease in the surface area of the soil. However, no clear difference in the shape and roughness of quartz was found after the nZVI treatment. This study was performed to improve the understanding of mass transfer from nZVI to inert solid particles in soil and its effect on soil improvement.